Junín virus induces autophagy in human A549 cells - Perez Vidakovics, Maria Laura Anabella (2019)
Autophagy, a highly regulated degradative process that promotes cellular homeostasis, is increasingly recognised as a fundamental component of the cellular response against viral infection. In this study, we investigated the role of autophagy during Junín virus (JUNV) multiplication using human A549 cells. We found that JUNV infection induces an increment of the LC3-II/LC3-I ratio, an accumulation of punctate pattern in RFP-LC3-transfected cells and the colocalisation of viral nucleoprotein and LC3 protein, suggesting autophagosome formation. JUNV infection also induced the degradation of the autophagy receptor p62, suggesting that complete autophagic flux was triggered. In addition, we showed that inhibition of autophagy with bafilomycin A1 or 3-methyladenine significantly reduces viral multiplication. Moreover, viral yield was increased when autophagy was induced using rapamycin. Furthermore, JUNV infection induced the colocalisation of p62, ATG16, RAB5, RAB7A and LAMP1 with the autophagosomal LC3 protein. That suggests that phagosomes undergo the maturation process during viral infection. Finally, we demonstrated that siRNA experiments targeting essential autophagy genes (ATG5, ATG7 and Beclin 1) reduce viral protein synthesis and viral yield. Overall, our results indicate that JUNV activates host autophagy machinery enhancing its multiplication.